Pengembangan Jaringan Kolaborasi Mahasiswa Pelaku Industri Kreatif Fashion dan Peran Pengabdian Kepada Masyarakat Dalam Penguatan Ekosistem Bisnis IslamPengembangan Jaringan Kolaborasi Mahasiswa Pelaku Industri Kreatif Fashion dan Peran Pengabdian Kepada Masyarakat Dalam Penguatan Ekosistem Bisnis Islam - Dean Amri, Ary; Syukri Amri, Adi Ihsan; Fithriani Aira, Dian Mala; Wendry, Widya Sari; Yusra, Hilman (JPM MOCCI : Jurnal Pengabdian Masyarakat Ekonomi, Sosial Sains dan Sosial Humaniora, Koperasi, dan Kewirausahaan, 2025)
This article discusses the development of collaboration between students and the creative fashion industry to strengthen the Islamic business ecosystem. In addressing the challenges of globalization, this collaboration focuses on innovative fashion products aligned with Sharia principles. Community service programs include skill training, seminars on Islamic business ethics, and the promotion of halal products. The research results show that this collaboration enhances industry capacity, expands market access, and raises awareness of sustainable products. The article recommends strengthening collaboration networks, increasing training, and involving the community in developing fashion products that align with Islamic values.